Multiculturalism in East Asia : a transnational exploration of Japan, South Korea and Taiwan - Kim, Hyun Mee; Hsia, Hsiao-Chuan (Asian cultural studies: transnational and dialogic approaches., 2016)
"An examination of multiculturalism in East Asia using a transnational approach. The collection focuses in on Japan, Korea and Taiwan to examine key issues including policy, racial discourse, subjectivity and the implications for established ethic minority communities"--Provided by publisher